A New Framework for Building Participation in the Arts - McCarthy, Kevin F. (RAND Corporation, 2001)
Arts organizations across the country are actively expanding their efforts to increase public participation in their programs. This report presents the findings of a RAND study sponsored by the Wallace-Reader's Digest Funds that looks at the process by which individuals become involved in the arts and attempts to identify ways in which arts institutions can most effectively influence this process. The report presents a behavioral model that identifies the main factors influencing individual decisions about the arts, based on site visits to institutions that have been particularly successful in attracting participants to their programs and in-depth interviews with the directors of more than 100 institutions that have received grants from the Wallace-Reader's Digest Funds and the Knight Foundation to encourage greater involvement in the arts. The model and a set of guidelines to help institutions approach the task of participation building constitute a framework that can assist in devising participation-building approaches that fit with an institution's overall purpose and mission, its available resources, and the community environment in which it operates--in other words, a framework that will enable arts institutions to take an integrative approach to building participation in the arts.